The dielectric constant (ɛr =ɛ'r - jɛ"r) and loss tangent (tan δ = ɛ"/ɛ') of different thicknesses of 70% thermoplastic natural rubber-30% yttrium iron garnet (Y3FesO12) composite / Noor Azleen Azmi - Azmi, Noor Azleen (Faculty of Applied Sciences, 2017)
Thermoplastic natural rubber (TPNR) was prepared by melt-blending of polypropylene (PP) and natural rubber (NR) in weight percentage ratio of 70:30 using internal Rheomixer. Sample of Yttrium Iron Garnet (Y3FesOI2) filled TPNR was prepared at a fixed TPNR content (70% of the total weight). The effect of YIG content with two thicknesses on dielectric constant (Ɛr =Ɛ'r - jƐ"r) and loss tangent (tan [δ = Ɛ"/Ɛ') were studied. Dielectric constant and loss tangent were analyzed using PNA-L Network Analyzer in the frequency range of (8-12 GHz). The homogeneity of sample was verified using Pyris 1 Thermogravimetric Analyzer (Perkin Elmer). The samples prepared were pure TPNR, 2 mm and 5 mm YIG filled TPNR. The dielectric constant for 5 mm sample was higher than that of the 2 mm. On the other hand, the loss tangent for 2 mm sample was lower than that of 5 mm YIG filled TPNR. This composite shows the value of dielectric constant and loss tangent at the X-band. Hence, this research will help in increasing the value of Malaysian second crop which is natural rubber